Organizational indicators for CASE tools selection: a case study - Mendoza Morales, Luis Eduardo; Rojas, Teresita; Pérez, María A. (Revista Colombiana de Computación, 2001)
It is known that the selection, acquisition and implementation process of a CASE (Computer Aided Software Engineering) tool in an organization is a complex process. Fundamentally the impact of a tool is not simply the product of its inherent properties but also depends on the nature of the Information Systems (IS) development process and the organization thereof. Keywords: CASE tools, development process improvement, selection, evaluation, organizational indicators, Information Systems